KONSEP HABLUMMINALLAH DALAM LIRIK LAGU SANDARAN HATI LETTO - Eka Anjani; Fenny Mahdaniar (Ath Thariq Jurnal Dakwah dan Komunikasi, 2023)
The Song is a narrative literary work, as well as an effective communication medium. That’s because song can express notions and feelings and can last a long time. Not infrequently, songs are used as a means for musicians to convey da'wah messages. However, sometimes the language used by musicians does not always express explicit but implicit intentions, such as the Letto song "Sandaran Hati". To explore the implicit meaning holistically, this study uses Dilthey's hermeneutic analysis. Dilthey's typical hermeneutic analysis is to examine the erlebnis (living experience) and ausdruck (expression) aspects, to find a deep and objective verstehen (understanding) of the text made by the subject. This research method uses a descriptive qualitative method with literature study data collection and look-note analysis method. The findings of the study found that there are several hablumminallah concepts to be conveyed in the lyrics of Letto's song "Sandaran Hati", such as 1) Humans as servants of Allah who are equipped with thoughts and feelings in carrying out life in the world; 2) One of the duties of humans as a servant is to be a human being who is beneficial to those around him; 3) when humans experience problems in life both in the world and about religion, they can ask for Allah's guidance.